TOURISM AS AN AGENT TO TRANSFORM RURAL SOCIABILITY: AN APPROACH FROM HISTORY - Villalobos Cubero, Lissy Marcela (2012)
This item is the presentation of a model study (approximately) of rural tourism in Costa Rican society with a historical perspective from the articulators traits of sociability, taking into account a micro-macro (local-regional bound national interests, in turn embedded in a dynamic world) with a vision of history, it’s about the restructuring dimension generated by tourism in rural settings where Costa Ricans developed in the second half of the twentieth century